Integrated Urban Transport and Land-Use Policies in Reducing CO2 Emissions and Energy Consumption: Case Study of a Medium-Sized City in Thailand - Prinya Chindaprasirt; Pongrid Klungboonkrong; Sittha Jaensirisak; Natthapoj Faiboun; Sina Long; Atit Tippichai; Michael A. P. Taylor (My University, 2024)
In developing cities, transport activities have become one of the primary sources of CO2 emissions and energy consumption owing to rapid economic growth, urbanization, and motorization. Khon Kaen City, Thailand, was chosen as a representative mid-sized city of a developing country to investigate the potential influences of transit-oriented development (TOD), light rail transit (LRT), and electric vehicle (EV) policy integration scenarios on CO2 emission and energy consumption reductions in 2016, 2026, and 2046. The TOD did not significantly reduce CO2 emissions or energy consumption because it was only applied in one area of the city. The LRT development also had a small effect because of the small proportion of modal shifts to LRT. However, EV utilization offered the greatest potential for reducing both CO2 emissions and energy consumption. In addition, the integrated scenario combining the three policies had a promising effect, diminishing both CO2 emissions and energy consumption, because it gathered the potential merits and benefits of each individual policy.
Keywords: Consumption; Transportation Planning and Optimization